Multimodal analgesia with anapiron, nonsteriod anti-inflammatory drugs, local infiltrative anesthesia, and pregabalin in case of primary total hip arthroplasty - Bondarenko, Stanislav; Filipenko, Volodymyr; Lyzogub, Mykola; Badnaoui, Ahmed; Moysey, Artur; Lyzogub, Kseniia (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective: to evaluate the effectiveness of anesthesia, side effects and time to activation from the bed patients with hip joint arthritis of the IV stage after total hip arthroplasty using multimodal analgesia with Anapiron, nonsteriod anti-inflammatory drugs, local infiltrative anesthesia, and pregabalin compare to standard opioid analgetics. Methods: A prospective, randomized comparative study included 100 patients (age 51 to 72 years) with hip arthritis of the IV stage and different etiology after primary total hip arthroplasty. In the study group (50 patients) a protocol of multimodal analgesia was used: pregabalin 150 mg in the evening before surgery, then 150 mg twice a day for 5 days, intraoperative local infiltrative anesthesia of the hip joint region with a mixture (bupivacaine 0.25 % 40 ml, epinephrine 0.3 ml, ketorolac 30 mg, dexamethasone 4 mg); after the surgery — Anapirone 1 g, 6 times for 2 days; parecoxib 20 mg, 2 times during the day, then — dexketoprofen 50 mg in case of pain more than 3 points by VAS. In 50 patients of the control group after the surgery have been using opioid drugs parenterally and dexketoprofen 50 mg/day during 2–3 days. The pain syndrome was assessed according to VAS on days 1, 2 and 3 after the operation, also side effects and time to their-self rising from the bed. Results: in both groups effective anesthesia was achieved without significant difference in the parameter «pain syndrome». Side effects (nausea, vomiting, and dizziness) in the study group are much less common than in the control group. Patients of the control group rose their-self from the bed one day later than in the study group (p = 0.047). Conclusions: multimodal analgesia with Anapiron, nonsteriod anti-inflammatory drugs, local infiltrative anesthesia, and pregabalin in case of primary total hip arthroplasty allowed us to obtain effective analgesia, decrease the amount of side effects and promote early activation of patients compare to standard regimes with opioid analgetics.